The influence of wetting-drying alternation on methylmercury degradation in Guangzhou soil. (April 2020) - Xie, Mengying; Zhang, Caixiang; Liao, Xiaoping; Huang, Changsheng
Abstract: In one of our previous studies, the mechanisms of radical-initiated methylmercury (MeHg) degradation in soil with coexisting Fe and Cu have been reported. In this work, various environmental factors, including water table fluctuation, pH and major ions, are discussed to clarify the behavior of MeHg in subsurface environments. Soil column experiments were set up to simulate the degradation of MeHg in the soil with an iron-bearing mineral (annite), which has often undergone repeating wetting-drying cycles, resulting from the local climate. The results indicate that wetting-drying alternation can initiate MeHg degradation in the soil with the annite mineral. Additionally, the majority of the major ions (K +, Na +, Mg 2+, Fe 3+, Cl −, SO4 2−, NO3 − ) in the interstitial soil had little effect in the degradation of MeHg with the exception of Cu, which improved the degradation depending on the pH. At acidic pHs Cu increased the production of hydroxyl radical while at more alkaline pHs there was oxidation to Cu(III). The products including Hg(II) and Hg(0) of MeHg degradation were also identified in this work. This study reveals that the geochemical cycle of MeHg is closely linked to local climate and pedosphere processes. Graphical abstract: Image 1 Highlights: Iron-bearing mineral induced the degradation of methylmercury in soil columns. Wetting-drying alternation played a significant role in the abiotic degradation of MeHg. Local acid rain was an important influence factor for the MeHg degradation. Cu can promote the degradation of MeHg visa both facilitating the generation of .OH at acidic environment and forming Cu(III) at neutral or basic conditions. Abstract : Summary: Cu can improve the degradation of MeHg in soil through producing OH at acidic and generating Cu(III) at neutral and basic conditions.